The influence of mobile app in Glycemic Control and Prevention of Hypoglycemics in Diabetic management: A Systematic Review - Netha Damayantie; Muhammad Rusdi; Syamsurizal; Ummi Kalsum (OPI Napoli, 2022)
Introduction. The use of technology in the treatment of diabetes can facilitate the medium of communication between nurses and clients in data collection to create a comfortable life for patients. The use of mobile health technology in diabetic education is an innovative learning method that can engage patients and influence positive health behaviors. Aim. This study aims to find out the influence of mobile-based education applications in the Haemoglobin A1c control and prevention of hypoglycemia in patients with type 2 diabetes mellitus. Methods. Database search for article are from four databases such as Pubmed, Sciencedirect, Proquest, and Cochrane is limited to the publication of the last ten years from 2010 to 2021 and full text article in English. Authors individually screened the titles and abstracts, then full articles in order to obtain papers that met inclusion criteria Results. a total of 664 references were found. After duplicates were removed, 391 potentially relevant references remained from the database searches. Eight articles were finally designated as articles to be reviewed and use RCT design. Most studies put a Haemoglobin A1c (HbA1c) as a primary outcomes, and hypoglycemia as a secondary outcomes. Through the use of mobile app, there are reductions in HbA1c which affect the hypoglycemia events in Type 2 DM patients. Conclusion. Mobile application can enhance HbA1c and hypoglycemia control among T2DM patients. Because providing patient education face to face is time-consuming, the use of mobile application may be an effective complement or alternative for healthcare professionals to manage the rapidly increasing number of diabetes patients.